Cuidados de enfermería en pacientes con Síndrome de Guillain Barré. Ecuador, 2018 - Unach (2019)
Nursing care is relevant in Guillain Barré Syndrome, currently they are not yet standardized, because it is a pathology of idiopathic cause that appears after a viral or bacterial infection, with a global incidence of 1 to 4 cases per every 100,000 inhabitants, this pathology being the most frequent of acute flaccid paralysis. The objective of this study was to systematize nursing care in patients with Guillain Barré syndrome, according to the criteria of different authors. The research is a bibliographical review of a descriptive nature that was made using the technique of documentary analysis contemplated in the period 2009 to 2019, for which a population of 150 research works was taken with a real sample 40 selected articles, which were cited to through search engines such as BIREME, E-BOOK, PubMED, PROQUEST and BOOKSMEDICOS, Google Scholar, with access to indexed pages such as: Scielo, MedLine, four officers: from the World Health Organization (WHO), Ministry of Public Health (MSP) It is concluded that nursing care can be systematized according to the needs of the patient, projecting nursing diagnoses typical of the Taxonomy North American Nursing Diagnosis Association (NANDA), to select objectives that allow to plan timely and effective interventions to meet the needs in Syndrome by Guillain Barré.